1992
DOI: 10.1089/cap.1992.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Neuroleptic Malignant Syndrome in Children and Adolescents: Two Case Reports and a Warning

Abstract: Neuroleptic malignant syndrome (NMS) is a potentially fatal disorder associated with the use of neuroleptics. Clinical research on NMS to date has focused exclusively on adults, but increasing numbers of juvenile cases have been reported. Two cases of juvenile NMS treated by the authors are discussed to demonstrate early warning signs, possible contributory factors, and effective treatment strategies. Forty-nine reported cases of NMS in children and adolescents are then reviewed in order to assess frequency, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…These observations may have some relationship to clin ical observations that indicate that children may be at relatively high risk for developing neuroleptic malig nant syndrome (NMS) during neuroleptic treatment. In children less than 6 years of age, almost all reported cases of NMS occurred after ingestion of only a single dose of neuroleptic (Latz and McCracken 1992). The fa tality rate from NMS was 13% among adolescent pa tients with NMS (n = 38), and 33% in patients 12 years or younger (n = 11) (Latz and McCracken 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations may have some relationship to clin ical observations that indicate that children may be at relatively high risk for developing neuroleptic malig nant syndrome (NMS) during neuroleptic treatment. In children less than 6 years of age, almost all reported cases of NMS occurred after ingestion of only a single dose of neuroleptic (Latz and McCracken 1992). The fa tality rate from NMS was 13% among adolescent pa tients with NMS (n = 38), and 33% in patients 12 years or younger (n = 11) (Latz and McCracken 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In children less than 6 years of age, almost all reported cases of NMS occurred after ingestion of only a single dose of neuroleptic (Latz and McCracken 1992). The fa tality rate from NMS was 13% among adolescent pa tients with NMS (n = 38), and 33% in patients 12 years or younger (n = 11) (Latz and McCracken 1992).…”
Section: Discussionmentioning
confidence: 99%
“…There appear to be two dramatically different outcomes of NMS in children and adolescents: complete recovery or death. In their series of 49 cases, Latz and McCracken (1992) found that 16% of patients died. Of the 35 cases reviewed by Steingard and colleagues (1992), 14% died.…”
mentioning
confidence: 96%
“…In their case report, Steingard et al describe a 16-year-old who developed the cardinal symptoms and signs of NMS: altered mental status (e.g., agitation, disorientation), fever, increased muscle tone or rigidity, autonomie instability (e.g., elevated blood pressure), leukocytosis, elevated creatinine phosphokinase (CPK) levels, and abnormal liver function studies [e.g., elevated levels of enzymes such as serum glutamic oxaloacetic transaminase (SGOT)]. Latz and McCracken (1992) reported on two adolescents, ages 15 and 16 years, who presented with a classical symptom constellation. Neither group found evidence of a different presentation of NMS in younger children.…”
mentioning
confidence: 99%
See 1 more Smart Citation